Is social security secure with NDC? - Tito Boeri; Vincenzo Galasso (Institute for the Study of Labor (IZA), 2010)
The introduction of NDC public pension scheme in few European countries, such as Latvia, Sweden, Italy, and Poland, in the nineties was motivated, among other things, by the need (i) to ensure the long term financial sustainability of the public pension system by linking pension returns to economic growth; (ii) to reduce the existing distortions in the labor market, due to the existing strong incentives to retire early, (iii) to increase the intergenerational equity of the system, jeopardized by the different returns across generations; and (iv) to reduce the systematic political interference with public pension systems under aging through the introduction of a sequence of automatic adjustments in the system that do not require government intervention. After more than ten years from their introduction, these systems have performed reasonably well on these accounts. However, some degree of political involvement with the working of the pension systems has continued (f.e., in Italy), and new concerns have emerged. In particular, the combination of a pension system, which strongly bases the benefit calculation on previous contributions (and on thus labor market status), and the existence in some countries of a dual labor market, with young workers being held on the margin of the regular labor market for many years, create a new, potentially strong challenge to these systems. Our simulations of the future pension benefits for the current generation of young workers with a discontinuous working history in Italy and Sweden suggest that the replacement rates will be low, unless the retirement age is significantly increased. This effect may end up jeopardizing the political sustainability of these NDC systems in the future, unless important labor market reforms are introduced. We discuss the effects on the future generation of retirees in Italy and Sweden of a current labor market reform: the introduction of a unique labor market contract, aimed at reducing the dualism between temporary and permanent workers.
Keywords: J26; J68; 330; notional defined contribution; pay as you go; labor market dualism and pensions